Genome-wide association study for mandibular prognathism using microsatellite and pooled DNA method - Saito, Fumio; Kajii, Takashi S.; Oka, Akira; Ikuno, Keiichiro; Iida, Junichiro (American journal of orthodontics and dentofacial orthopedics, 2017)
The purpose of this study was to extend an association study from chromosome 1 to the whole genome (genome-wide association study) to find susceptibility loci of mandibular prognathism. Two hundred forty patients diagnosed with mandibular prognathism and 360 healthy controls of Japanese descent were recruited. The typing of microsatellites covering the whole genome was conducted using a pooled DNA method. Upon completion of the first and second screenings with pooled DNA, the positive microsatellite markers from both the first and second typings were retyped using individual-subject DNA samples to confirm the significance of allele frequency. Six microsatellites (D1S0411i, D1S1358i, D3S0810i, D6S0827i, D7S0133i, and D15S0154i) showed differences between allele frequencies of the subjects and controls at P <0.001. D1S0411i, D1S1358i, D3S0810i, D6S0827i, D7S0133i, and D15S0154i were located on chromosomes 1p22.3, 1q32.2, 3q23, 6q23.2, 7q11.22, and 15q22.22, respectively. SSX2IP, PLXNA2, RASA2, TCF21, CALN1, and RORA were suggested as candidate genes. The genome-wide association study using microsatellites suggested that 6 loci (1p22.3, 1q32.2, 3q23, 6q23.2, 7q11.22, and 15q22.22) were susceptibility regions of mandibular prognathism. The locus 1p22.3 was supported by a previous linkage analysis, and the other 5 were novel loci. •Six microsatellites showed differences in allele frequency between subjects and controls.•Six loci of chromosome were susceptibility regions of mandibular prognathism.•One locus was supported by a previous linkage analysis, and the other 5 were novel.